Insights into the catalytic mechanism of dehydrogenase BphB: A quantum mechanics/molecular mechanics study. (October 2018) - Zhang, Ruiming; Shi, Xiangli; Sun, Yanhui; Zhang, Qingzhu; Wang, Wenxing
Abstract: The present study delineated the dehydrogenation mechanism of cis -2, 3-dihydro-2, 3-dihydroxybiphenyl (2, 3-DDBPH) and cis -2, 3-dihydro-2, 3-dihydroxy-4, 4′-dichlorobiphenyl (2, 3-DD-4, 4′-DBPH) by Pandoraea pnomenusa strain B-356 cis -2, 3-dihydro-2, 3-dihydroxybiphenyl dehydrogenase (BphB) in atomistic detail. The enzymatic process was investigated by a combined quantum mechanics/molecular mechanics (QM/MM) approach. Five different snapshots were extracted and calculated, which revealed that the Boltzmann-weighted average barriers of 2, 3-DDBPH and 2, 3-DD-4, 4′-DBPH dehydrogenation processes are 10.7 and 11.5 kcal mol −1, respectively. The established dehydrogenation mechanism provides new insight into the degradation processes of other chlorinated 2, 3-DDBPH. In addition to Asn115, Ser142, and Lys149, the importance of Ile 89, Asn143, Pro184, Met 187, Thr189, and Lue 191 during the dehydrogenation process of 2, 3-DDBPH and 2, 3-DD-4, 4′-DBPH were also highlighted to search for promising mutation targets for improving the catalytic efficiency of BphB. Graphical abstract: Image 1 Highlights: The dehydrogenation mechanism of 2, 3-DDBPH and 2, 3-DD-4, 4′-DBPH by dehydrogenase BphB is investigated by QM/MM method. The Boltzmann-weighted averaging method was employed to obtain potential barriers from five different snapshots. Ser142, Asn143 and Lys159 are identified as key residues.